Death wish [videorecording (DVD)] - Hancock, Herbie, 1940- (Paramount Pictures, 2017)
After his wife and daughter are violently attacked by a gang of thugs in their apartment, Paul Kersey turns vigilante, and stalks the mean streets of New York on the prowl for muggers, hoodlums, and the like.